Tumor Microenvironment Heterogeneity-Based Score System Predicts Clinical Prognosis and Response to Immune Checkpoint Blockade in Multiple Colorectal Cancer Cohorts - Wang, Hufei; Li, Zhi; Ou, Suwen; Song, Yanni; Luo, Kangjia; Guan, Zilong; Zhao, Lei; Huang, Rui; Yu, Shan (Frontiers in Molecular Biosciences, 2022)
Despite tumor immunotherapies by immune checkpoint blockade (ICB) having made great achievements, only a small percentage of colorectal cancer patients respond to immune checkpoint therapy. Identification of these patients will facilitate ICB application in colorectal cancer (CRC). In this study, we integrated multiple CRC cohorts (2078 samples) to construct tumor microenvironment (TME) subtypes using TME indices calculated by CIBERSORT and ESTIMATE algorithm. Furthermore, a surrogate quantitative indicator, the tumor microenvironment immune genes (TMEIG) score system was established using the key immune genes between TME cluster 1 and TME cluster 2. The subsequent analysis demonstrated that TME subtypes and TMEIG score system were correlated with clinical outcomes of patients in multiple CRC cohorts and exhibited distinct immune statuses. And Tumor Immune Dysfunction and Exclusion (TIDE) analysis indicated that patients with low TMEIG scores were more likely to benefit from ICB therapy. Two ICB cohorts (GSE78220 and IMvigor210 cohorts) also validated that low TMEIG score patients had higher ICB response rates and exhibited better prognosis under ICB treatment. The biomarker evaluation module on the TIDE website revealed that the TMEIG score was a robust predictive biomarker. Moreover, differential expression analysis, immunohistochemistry, qPCR experiments and gene set prioritization module in TIDE website showed the five genes that constitute of TMEIG score system (SERPINE1, FABP4, SCG2, CALB2, HOXC6) were closely associated with tumorigenesis, immune cells, and ICB response indices. In conclusion, the novel TMEIG score could accurately predict the prognosis and ICB response of CRC patients. SERPINE1, FABP4, SCG2, CALB2, and HOXC6 might be potential targets related to ICB treatment. And our study provided new insights into precision ICB therapy in colorectal cancer.